Chastity, Self-Control, and Abstinence in the Digital Age: Quranic, Hadith, and Psychological Perspectives on the Effects of Social Media (Journal of the Sociology and Theory of Religion, 2026)
In the digital age, chastity, self-control, and abstinence face unprecedented challenges. To what extent can religious awareness preserve these values in the face of the influence of social media? Can repeated exposure to digital content transform individuals’ ethical perceptions, weakening principles that the Qur’an and the Hadiths present as fundamental? What role does psychology play in explaining the tension between faith, desire, and online behavior? Using a descriptive-analytical approach and opinion surveys, this study explores whether religious guidance remains an effective instrument for promoting moral change and reinforcing dignity in contemporary society.
Keywords: Religious awareness; Chastity; Values; Social media; Abstinence; the Qur’an; the Hadiths; Psychology